Penentuan Lokasi Kantor Cabang Laboratorium Lingkungan Hidup Menggunakan Metode Center of Gravity di Provinsi Jawa Barat - Hamdani Aris Sudrajat (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
West Java Province is one of the largest industrial areas in Indonesia. However, there is a threat that can paralyze industrial activity in West Java, one of the threats associated with environmental quality. An important aspect that affects the effective and efficient management of the environment in the area is laboratory. PT. Unilab Perdana is an environmental lab service company established since 1990 and located in South Jakarta. Looking at the state of West Java, the company is keen to develop its business by opening a branch in West Java Province. Opening a new branch location or location factor is an important factor. Therefore, this study is a study to determine the location of branch offices with the approach of the Gravity Center method to determine the preferred location based on PT. Unilab Perdana. The results showed coordinate centers at 6 ° 27 '15 .0516 'S and 107 ° 20' 2.9364 E E, located in Mulyasejati, Ciampel, Karawang district, West Java.